A Graphitic‐C3N4 "Seaweed" Architecture for Enhanced Hydrogen Evolution. Issue 39 (15th July 2015) - Han, Qing; Wang, Bing; Zhao, Yang; Hu, Chuangang; Qu, Liangti
Abstract: A seaweed‐like graphitic‐C3 N4 (g‐C3 N4 "seaweed") architecture has been prepared by direct calcination of the freeze‐drying‐assembled, hydrothermally treated dicyandiamide fiber network. The seaweed network of mesoporous g‐C3 N4 nanofibers is favorable for light harvesting, charge separation and utilization of active sites, and has highly efficient photocatalytic behavior for water splitting. It exhibits a high hydrogen‐evolution rate of 9900 μmol h −1 g −1 (thirty times higher than that of its g‐C3 N4 bulk counterpart), and a remarkable apparent quantum efficiency of 7.8 % at 420 nm, better than most of the g‐C3 N4 nanostructures reported. This work presents a very simple method for designing and developing high‐performance catalysts for hydrogen evolution. Abstract : Weeding out hydrogen : A straightforward template‐free freeze‐drying method affords a graphitic‐C3 N4 "seaweed" architecture of one‐dimensional mesoporous fibers. This seaweed architecture has a highly efficient photocatalytic activity for hydrogen evolution from water under visible‐light irradiation that is better than most reported nanostructured g‐C3 N4 catalysts.